2018
DOI: 10.5935/0103-507x.20180069
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons and correlations of pain intensity and respiratory and peripheral muscle strength in the pre- and postoperative periods of cardiac surgery

Abstract: ObjectiveTo evaluate respiratory and peripheral muscle strength after cardiac surgery. Additionally, we compared the changes in these variables on the third and sixth postoperative days.MethodsForty-six patients were recruited, including 17 women and 29 men, with a mean age of 60.50 years (SD = 9.20). Myocardial revascularization surgery was performed in 36 patients, replacement of the aortic valve in 5 patients, and replacement of the mitral valve in 5 patients.ResultsA significant reduction in respiratory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
0
18
0
3
Order By: Relevance
“…De Menezes et al [ 20 ] reported that reduced RMS was associated with decreased functional capacity and an increased period of recovery of lung function, as it is directly related to peripheral muscle strength. Therefore, improvement in RMS can improve FVC and FEV 1 and thereby the 6-minute walking distance.…”
Section: Discussionmentioning
confidence: 99%
“…De Menezes et al [ 20 ] reported that reduced RMS was associated with decreased functional capacity and an increased period of recovery of lung function, as it is directly related to peripheral muscle strength. Therefore, improvement in RMS can improve FVC and FEV 1 and thereby the 6-minute walking distance.…”
Section: Discussionmentioning
confidence: 99%
“…Está associada à piora da independência funcional e à recuperação cirúrgica retardada. Seu adequado manejo pode contribuir para reduzir o tempo de internação hospitalar e diminuir taxas de complicação no período pós-operatório (37)(38)(39)(40) .…”
Section: Discussionunclassified
“…Studies have evaluated the correlation between preoperative anxiety and postoperative pain in several surgical procedures [5][6][7]. In the postoperative period of cardiac surgeries, which are complex and large procedures, pain has still been shown to be very frequent, as indicated by several studies [8][9][10][11][12][13]. It is evident that uncontrolled postoperative pain prevents functional recovery, decreases the patient's quality of life, becomes a risk factor for persistent postoperative pain, chronic pain and disability, in addition to evidencing a low quality of care [14].…”
Section: Trial Registrationmentioning
confidence: 99%